Alisher Navoi and the 21st Century (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2026)
The article extensively explores Alisher Navoi, one of the greatest figures, and his role in the 21st century. The main objective of the study is to analyze Navoi’s place in world literature, his scholarly and artistic legacy, as well as the current priority policies of spiritual education being implemented in Uzbekistan. Additionally, the article presents the perspectives of participants from an international scientific-theoretical conference, including Navoi scholars and literary researchers from various countries. In my personal opinion, the study should highlight the importance of teaching Navoi’s works in higher education institutions, the systematic research conducted in the field of Navoi studies, and their role in developing national spirituality, giving special attention to these aspects.